Normas Voluntárias de Sustentabilidade (NVS) e implicaç\~oes sobre as exportaç\~oes de produtos do agronegócio: Frutas - Michelle Márcia Viana Martins; Scarlett Queen Almeida Bispo; Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study examines the importance of Voluntary Sustainability Standards (VSS) in increasing Brazilian fruit exports. The adherence of producers to VSS is crucial due to the sensitivity of these products to quality, food safety, and sustainability, especially for accessing developed importing markets. Certification is nearly indispensable for producers to participate in the international market, and knowledge of certification requirements is essential to enhance Brazil's participation in this market. The study focuses on Brazilian fruit chains, identifies products with commercial potential, such as tropical fruit cultivation, and highlights six fruits with a higher share in exports: melon, grape, papaya, Brazil nut, mango, lemon, and lime. Interviews were conducted with producers, cooperatives, and public and private institutions to understand the complexity of certification systems and their implications in fruit trade. The globalization of agri-food systems and the demand for safe and sustainable food drive the adoption of certification programs that ensure sustainability, control, and traceability in the production chain, becoming indispensable requirements for export. The investigated certifications encompass environmental, social, management, ethical, and quality criteria, which vary among certifying bodies.
Keywords: F13; F18; F17; 330; VSS; Brazilian fruit exports; certifications; private standards; Global G.A.P.; integrated fruit production